Knowledge and usage of Child Health and Development Records by mothers with a single child attending Teaching Hospitals near Colombo - Dahanayake, S.A.; Cooray, N.M.J.; Darshani, J.P.N.; Gunatilake, M. (My University, 2012)
The Child Health and Development Record (CHDR) is a book documenting an individual child’s health history including growth, immunization, nutrition and developmental milestones from birth till 14 years of age and is an important tool in enhancing communication between health care workers and parents. Sri Lanka allocates a significant portion of its health budget to issue free CHDRs to all newborn children to improve their quality of life, and the outcome of this effort rests upon the knowledge and usage of it by all mothers which needs frequent monitoring to maintain a successful and productive programme.